Avaliação da viabilidade econômico-financeira do transporte intermodal de automóveis: um estudo de caso - Rodrigo de Abreu Vieira (2015)
The Brazilian transport network is significantly unbalanced, when compared to other countries of similar size, like Russia, Canada, USA, and Australia. This result is aggravated by the low investments in national transport infrastructure after the 70s. The road mode is predominant in Brazil in detriment to others, even when cargo is transported over long distances, where this method is less efficient. Aiming to counter this reality and to demonstrate technical and financial parameters that envisage the use of other transport modes in cargo logistics operations, this dissertation examined the feasibility of using railroad and cabotage for the transportation of new cars, from the plants to their respective dealers. To this end, it guide itself in the analysis of vehicle transportation operations currently performed in Brazil and abroad, in the current traffic capacity of the railway and port sectors, in the selection of the most suitable equipment in the use of intermodality, in road, rail and sea costs analysis in order to evaluate the feasibility of the suggested operations. This study differs from others because of its proposition and financial evaluation for the implementation of road-rail intermodality or for the use of cabotage in car transportation, through equipment and operation that are usual abroad, but still not seen in Brazil. The case study for model validation was an automaker, located in the state of São Paulo, and its dealers in the state of Pernambuco. The results depict potential economic gain in the two alternatives considered railroad and cabotage compared to how the car transportation is currently performed. The research of new technologies in the logistics area aim to modernize the transport, reducing costs and increasing reliability, efficiency and security of both cargo and people.